Literature Review: Relationship of Lifestyle with Incidence of Primary Dysmenorrhea in College Students - Maharani, Maharani; Khumairoh, Rizzatul (Asian Journal of Health Research, 2024)
Introduction: Menstruation is periodic and cyclic bleeding from the uterus, accompanied by endometrial desquamation. In specific individuals, menstruation can cause pain called dysmenorrhea, which is characterized by mild, moderate, and severe menstrual pain. Primary dysmenorrhea is not a life-threatening disorder, but it can hurt women's quality of life. Prevalence of menopause in Indonesia An estimated 55% of women of reproductive age experience pain during menstruation. Material and Methods: We searched articles published from 2014-2020 in  PubMed, Proquest, and Google Scholar with the keywords "primary dysmenorrhea” AND “student lifestyle”. All data were gathered and analyzed. Results: The results showed that 8 articles showed the relationship between lifestyle and the occurrence of primary menstrual pain among female students. In comparison, the other two articles show that there is no relationship between lifestyle and primary dysmenorrhea in female students. Conclusion: This study concludes that an unhealthy lifestyle, such as high stress levels, infrequent exercise, and frequent consumption of fast food, is effective for primary dysmenorrhea during menstruation.